Multifunctional reversibly sealable microfluidic devices for patterned material deposition approaches - Gang, A.; Haustein, Natalie; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni) (RSC Advances, 2015)
We present a concept to produce reversibly sealable polydimethylsiloxane (PDMS) based microfluidic devices with versatile channel designs, withstanding pressures up to 600 kPa. A novel fabrication strategy, namely the casting of a secondary PDMS casing around the initial channel system allows diverting the tubing attached to the channels sideways so that a simple mounting assembly can be used to press the fluidic chip onto virtually any type of substrate. We demonstrate the functionalities of the developed setup at a proof-of-concept level by direct printing of electronic interconnects onto flexible substrates in a single step. As a second application, we generate uniquely shaped polymer structures when combining the presented technique with droplet microfluidics using a UV-curable adhesive and water as continuous and dispersed phases, respectively. We believe the developed approach has a plethora of applications and a clear perspective of being used for cost-efficient and multifunctional designs of novel classes of materials and devices in diverse areas from electronics to biotechnology.
CRIS-Team Scopus Importer:2023-03-20